Realistic Outcomes of Moon–Moon Collisions in Lunar Formation Theory - Uri Malamud; Hagai B. Perets (The Astrophysical Journal)
The multiple impact hypothesis proposes that the Moon formed through a series of smaller collisions, rather than a single giant impact. This study advances our understanding of this hypothesis, as well as moon collisions in other contexts, by exploring the implications of these smaller impacts, employing a novel methodological approach that combines self-consistent initial conditions, hybrid hydrodynamic/ N -body simulations, and the incorporation of material strength. Our findings challenge the conventional assumption of perfect mergers in previous models, revealing a spectrum of collision outcomes including partial accretion and mass loss. These outcomes are sensitive to collision parameters and the Earth’s tidal influence, underscoring the complex dynamics of lunar accretion. Importantly, we demonstrate that incorporating material strength is important for accurately simulating moonlet-sized impacts. This inclusion significantly affects fragmentation, tidal disruption, and the amount of material ejected or accreted onto the Earth, ultimately impacting the Moon’s growth trajectory. By accurately modeling diverse collision outcomes, our hybrid approach provides a powerful new framework for understanding the Moon’s formation. We show that most collisions (≈90%) do not significantly erode the largest moonlet, supporting the feasibility of lunar growth through accretion. Moreover, we revise previous estimates of satellite disruption, suggesting a higher survival rate and further bolstering the multiple-impact scenario.